Multidecadal fluctuations in green turtle hatchling production related to climate variability - Pablo del Monte-Luna; Miguel Nakamura; Vicente Guzmán-Hernández; Eduardo Cuevas; Melania C. López-Castro; Francisco Arreguín-Sánchez (Scientific Reports, 2023)
Abstract The state of Campeche, Mexico, harbors one of the largest green turtle (Chelonia mydas) rookeries of the Wider Caribbean Region. Since the 1970s, harvesting of this population was common practice, but it has since ceased, and the population is rebounding as a consequence. In this rookery, during the past 37 years (1984–2020), the positive relationship between the annual number of nesting females and the number of hatchlings they produce has revealed a long-term population signal that we postulate could be related to environmental factors. To investigate this relationship more deeply, we adopt a stock-recruitment (SR) approach, which is commonly used in fisheries. Regression analysis methods for the SR relationship, including a dynamic version of the model that incorporates the effect of sea surface temperature, show that the number of recruits produced and the number of hatchlings per unit nester were significantly and inversely correlated with a 26-year cycle of the Atlantic Multidecadal Oscillation (AMO) with a three year lag. A possible explanation for this finding is that environmental conditions during warming periods of the 26-year AMO cycle may negatively affect hatchling production by altering the nest moisture content during the incubation period, and increasing embryonic mortality, while the annual female abundance at nesting beaches may decrease due to trophic effects. The time series of abundance corresponding to other population units of green turtles as well as other species of sea turtles in the Gulf of Mexico present a similar behavior to that evaluated here, suggesting a basin-wide environmental effect.